DMFT and PUFA Indices in First Permanent Molars of Iraqi Children in Najaf City - Ansam Mahdi Khalel; Mustafa Basim Ali; Maytham Adil Sadiq; Salah M. Ibrahim; Shatha Hameed Ali (University Library System, University of Pittsburgh, 2024)
Objective: To determine the prevalence and severity of caries in the first permanent molars of children aged 8 to 10 years in Najaf, Iraq. Subjects and Methods: This was a cross-sectional survey involving 1232 children aged 8 to 10 years in schools in Najaf, Iraq. Caries was assessed using the DMFT index and caries severity of permanent teeth was assessed using the PUFA index. Results: The prevalence of caries in the first permanent molars was 56.1% (n=691). The caries severity of the first permanent molars (PUFA index) was 38.7%, meaning that the children have more severe caries in the first permanent molars. Conclusion: Caries prevalence and severity increased with age and was high in first permanent molars.